That Squeezing Feeling : The Interest Burden and Public Debt Stabilization - Debrun, Xavier (IMF Working Papers; Working Paper ;, 2013)
The paper explores the extent to which the pressure of debt service on other spending items may push governments to embark on fiscal consolidation beyond what is strictly necessary to secure solvency. The empirical analysis identifies thresholds of interest bill indicators beyond which governments appear to shift to policies aimed at durably curbing the debt trajectory. Hence, in the current context of high inherited public debts, countries experiencing rising borrowing costs and interest payments would be more likely to enact more aggressive fiscal consolidations than warranted by strict solvency concerns. Conversely, those benefiting from persistently low interest rates despite rising debt stocks would likely opt for a more gradual fiscal consolidation path than what solvency considerations would normally dictate.